Examining the clinical relevance of metformin as an antioxidant intervention - Buczyńska, Angelika; Sidorkiewicz, Iwona; Krętowski, Adam Jacek; Adamska, Agnieszka (Frontiers in Pharmacology, 2024)
In physiological concentrations, reactive oxygen species (ROS) play a vital role in regulating cell signaling and gene expression. Nevertheless, oxidative stress is implicated in the pathogenesis of numerous diseases and can inflict damage on diverse cell types and tissues. Thus, understanding the factors that mitigate the deleterious effects of oxidative stress is imperative for identifying new therapeutic targets. In light of the absence of direct treatment recommendations for reducing oxidative stress, there is a continuing need for fundamental research that utilizes innovative therapeutic approaches. Metformin, known for its multifaceted beneficial properties, is acknowledged for its ability to counteract the adverse effects of increased oxidative stress at both molecular and cellular levels. In this review, we delve into recent insights regarding metformin's antioxidant attributes, aiming to expand its clinical applicability. Our review proposes that metformin holds promise as a potential adjunctive therapy for various diseases, given its modulation of oxidative stress characteristics and regulation of diverse metabolic pathways. These pathways include lipid metabolism, hormone synthesis, and immunological responses, all of which may experience dysregulation in disease states, contributing to increased oxidative stress. Furthermore, our review introduces potential novel metformin-based interventions that may merit consideration in future research. Nevertheless, the necessity for clinical trials involving this drug remains imperative, as they are essential for establishing therapeutic dosages and addressing challenges associated with dose-dependent effects.